Chemical, physico-mechanical properties and biological durability of rubberwood particleboards after post heat-treatment in palm oil - Seng, Hua Lee; Ashaari, Zaidon; Wei, Chen Lum; Aik, Fei Ang; Abdul Halip, Juliana; Halis, Rasmina (Walter de Gruyter GmbH, 2017)
The chemical properties, dimensional stability, mechanical strength and termite resistance of urea formaldehyde (UF) bond rubberwood (RW) particleboard (PB) were assessed after a two-step oil heat treatment (OHT). The PB was immersed in palm oil before heating to 180, 200, and 220°C in a laboratory oven for 2 h. Anti-swelling efficiency (ASE) and water repellency efficiency (WRE) as well as bending (MOE, MOR) and internal bonding strength (IB) were determined. Resistance against a subterranean termite, Coptotermes curvignathus Holmgren, was tested. The degradation of hemicelluloses and cellulose, that are mainly responsible for wood wetting processes, was confirmed by Fourier transform infrared (FTIR) spectra. Formation of an elevated cross-linking density in lignin also contributed to the dimensional stability, where 93.6% ASE and 46.3% WRE were achieved in the samples treated at 220°C. Mechanical properties of treated samples were inferior to the control samples due to hemicelluloses degradation and breakage of the UF bonding network. A significant improvement in termite resistance has been found in the treated samples.